Relation among Processes of Human Resources and Obtaining the Organizational Axial Capability with intermediation role of knowledge management based on modeling structural equations - Nazarpour, Mohammad; Shirin, Zahra Bostan (International Review of Management and Marketing, 2017)
Objective of this research is to review the intermediation role of knowledge management in relation among processes of human resources and obtaining organizational axial competency in Khuzestan general directorate of ports and Maritime - special economic zone of the Imam Khomeini port. In this research which was performed with descriptive method, 150 persons from directors and experts of this organization as sample were selected and studied randomly by simple random method based on Cochran formula. Information collection tools is researcher-built questionnaire that in this research, its face and content validity were confirmed based on literature review and judgment of the experts and reliability coefficient was computed and confirmed through Cronbach Alpha. The results of this research based on structural equations showed that with knowledge management in organization, we can take steps in parallel with improvement of processes of human resources and axial capabilities of the organization and this important note may be considered as stable competitive advantage for the organization. By improving the knowledge management, the organizational structures of planning process are protected and the organization provides the operation possibility from individual capabilities of the personnel and causes the personnel make effort to supply the customers’ requirements and the mentioned matters are steps in parallel with improvement of organizational performance and benefiting all potentialities of human resources in organizations. Keywords: Knowledge management, Processes of human resources, Axial capability of the organization JEL Classifications: D83, O15